Pelatihan Akupresure pada Kader Kesehatan Kecamatan Sijuk di Kabupaten Belitung Sebagai Daerah Kepulauan - R Ade Sukarna; Syamsul Rizal Sinulingga; Nazliansyah Nazliansyah; Sri Yani; Adelia Rivanti (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
Hypertension, or high blood pressure, is one of the global health problems whose prevalence continues to increase. Sijuk sub-district includes several villages, the number of people with hypertension reached 8,449 people, the third most in Belitung Regency. The purpose of this community service is to increase the independence and ability of health cadres in overcoming hypertension in the working area of Pukesmas Tanjung Binga, Sijuk District, Belitung Regency. The methods used are lecture, question and answer, demonstration and redemonstration. The activity was carried out in 3 stages, preparation, implementation and monitoring, with the target of 27 health cadres of Sijuk sub-district from 5 villages under the working area of Tanjung Binga Health Center. The activities carried out include one day cadre training with hypertension, TOGA, acupressure and acupressure practicum. The activity ended with an inter-village quiz.  After the training, the activity continued with monitoring in the form of visits to the work area of the health cadres. This visit takes place after 2 weeks to 1 month after the training, depending on the posyandu activities and cadre meetings in each village. Community Service Results. Evaluation results were taken at the time of training to assess knowledge and skills. The average increase in knowledge was 32%. The category of knowledge level before training, the number of less 48% and after training knowledge increased to 81%. Participants' post-training skill assessment scores increased by an average of 30%.